Analisis Kualitas Air Sungai Ukian Desa Mengwi Ditinjau Dari Aspek Lingkungan - I Kadek Widiantara (Program Studi Teknik Lingkungan Unmas Denpasar, 2021)
The Ukian River is one of the rivers flowing in the village of Mengwi which receives waste from agriculture, agriculture and domestic. A decrease in water quality is usually indicated by a change in water color and odor. This study aims to analyze the quality of river water in Ukian based on the quality standards of class II river water quality according to the Regulation of the Governor of Bali Number 16 of 2016 concerning environmental quality standards and standards for environmental damage standards. River water quality measurements were taken at 3 sampling locations. The parameters measured are BOD, COD, Lead (Pb) and Coliform. The results of research on the quality of river water in Ukian found that BOD from upstream to middle increased by 0.981 mg/l and decreased BOD levels by 0.101 mg/l from middle to downstream. From upstream to middle, COD levels increased by 1 mg/l and COD levels decreased by 3.717 mg/l from middle to downstream. Levels of lead (Pb) from upstream to middle increased by 0.345 mg/l and decreased levels of lead (Pb) by 0.345 mg/l from middle to downstream. Coliform levels from upstream to downstream were 11,000 mg/l.